THE TRAINING OF TIE-DYE HANDICRAFT IN “DURIAN SABATANG” STUDIO IN KAMANG MUDIK VILLAGE AGAM DISTRICT SUMATERA BARAT - Emridawati Emridawati; Yuniarti Munaf; Ulfa Salsabila (STKIP PGRI Sumatera Barat, 2019)
The training of tie-dye handicraft was the activity of community service toward the community of “Durian Sabatang” studio in Kamang Mudik village, Kamang Magek Sub-district, Agam District, Sumatera Barat. This training aims at empowering village people with their potentials so they can be trained with tie-dye skill. This training is also one of efforts to boost village people’s economy, whether the results of this training can be sold to the neighboring villages (tourism “Bantoroyo, Tirtasari”) or to the market. Methodologically, this community service was categorized as qualitative design so its data that were collected through observation were then described in the form of written/oral words. Hence it was very useful to know, comprehend, and study the data collected during the activities of this community service in order to obtain accurate results of this community service scientifically. These results were then described and arranged into scientific report according to the format of LPPMPP ISI Padangpanjang. This community service used the techniques of observation, interview, and documentation and the methods of lecture, demonstration, and practice.Result achieved in this community service was the high enthusiasm of the teenagers in “Durian Sabatang” studio highly trained during it. It can be seen from these teenagers’ work result namely creating table cloth, bag, shawl, blouse, shirt, handkerchief, and pillowslip by applying the technique of tie-dye into the white fabric of primissima, cotton, weaving, and calico. For the coloring, five kinds of Batik dye with the composition of blue (AS-D+BBB), pink (AS-BS+S.R), yellow (AS-G + M.B), orange (AS + M.GG), and red (AS + M.B). This training was fully conducted with good patience, seriousness, precision, and cooperation so the participants were successful in making the products. This good result has made the participants want to buy additional Batik materials and colors for retraining.